Research and development of III-V semiconductor surfaces for improved device interfaces - Lång, Jouko (fi=Turun yliopisto|en=University of Turku|, 2013)
This thesis is devoted to understanding and improving technologically important III-V compound semiconductor (e.g. GaAs, InAs, and InSb) surfaces and interfaces for devices. The surfaces and interfaces of crystalline III-V materials have a crucial role in the operation of field-effect-transistors (FET) and highefficiency solar-cells, for instance. However, the surfaces are also the most defective part of the semiconductor material and it is essential to decrease the amount of harmful surface or interface defects for the next-generation III-V semiconductor device applications. Any improvement in the crystal ordering at the semiconductor surface reduces the amount of defects and increases the material homogeneity. This is becoming more and more important when the semiconductor device structures decrease to atomic-scale dimensions. Toward that target, the effects of different adsorbates (i.e., Sn, In, and O) on the III-V surface structures and properties have been investigated in this work. Furthermore, novel thin-films have been synthesized, which show beneficial properties regarding the passivation of the reactive III-V surfaces. The work comprises ultra-high-vacuum (UHV) environment for the controlled fabrication of atomically ordered III-V(100) surfaces. The surface sensitive experimental methods [low energy electron diffraction (LEED), scanning tunneling microscopy/spectroscopy (STM/STS), and synchrotron radiation photoelectron spectroscopy (SRPES)] and computational density-functionaltheory (DFT) calculations are utilized for elucidating the atomic and electronic properties of the crucial III-V surfaces. The basic research results are also transferred to actual device tests by fabricating metal-oxide-semiconductor capacitors and utilizing the interface sensitive measurement techniques [capacitance voltage (CV) profiling, and photoluminescence (PL) spectroscopy] for the characterization. This part of the thesis includes the instrumentation of home-made UHV-compatible atomic-layer-deposition (ALD) reactor for growing good quality insulator layers. The results of this thesis elucidate the atomic structures of technologically promising Sn- and In-stabilized III-V compound semiconductor surfaces. It is shown that the Sn adsorbate induces an atomic structure with (1×2)/(1×4) surface symmetry which is characterized by Sn-group III dimers. Furthermore, the stability of peculiar ζa structure is demonstrated for the GaAs(100)-In surface. The beneficial effects of these surface structures regarding the crucial III-V oxide interface are demonstrated. Namely, it is found that it is possible to passivate the III-V surface by a careful atomic-scale engineering of the III-V surface prior to the gate-dielectric deposition. The thin (1×2)/(1×4)-Sn layer is found to catalyze the removal of harmful amorphous III-V oxides. Also, novel crystalline III-V-oxide structures are synthesized and it is shown that these structures improve the device characteristics. The finding of crystalline oxide structures is exploited by solving the atomic structure of InSb(100)(1×2) and elucidating the electronic structure of oxidized InSb(100) for the first time.